2021
DOI: 10.1017/s0033291721000751
|View full text |Cite
|
Sign up to set email alerts
|

Columbia-Suicide Severity Rating Scale Screen Version: initial screening for suicide risk in a psychiatric emergency department

Abstract: Background Suicide screening is routine practice in psychiatric emergency (PE) departments, but evidence for screening instruments is sparse. Improved identification of nascent suicide risk is important for suicide prevention. The aim of the current study was to evaluate the association between the novel Colombia Suicide Severity Rating Scale Screen Version (C-SSRS Screen) and subsequent clinical management and suicide within 1 week, 1 month and 1 year from screening. Methods Consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 43 publications
(56 reference statements)
1
46
0
2
Order By: Relevance
“…Recent findings have highlighted the limited predictive value of traditional approaches to assessing suicidal thinking and behaviors in real-world clinical settings, specifically the limitations of relying on endorsement of suicidal thinking. Both Bjureberg et al ( 1 ) and Simpson et al ( 2 ), utilizing large samples from psychiatric emergency departments with suicide outcomes at 30 and 365-days post-discharge, found the Columbia Suicide Severity Rating Scale (C-SSRS) screener to have poor predictive value. Similarly, ( 3 ) found that prior suicidal thoughts and behaviors only provided “marginal improvement in diagnostic accuracy above chance (p. 2).” In the largest meta-analysis to date, covering a span of 50 years, ( 4 ) similarly found: (a) that predictive value has not improved, (b) predictive values are only slightly better than chance across all outcome measures, (c) and ultimately called for fundamental changes in approach to suicide risk assessment, particularly across real-world clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have highlighted the limited predictive value of traditional approaches to assessing suicidal thinking and behaviors in real-world clinical settings, specifically the limitations of relying on endorsement of suicidal thinking. Both Bjureberg et al ( 1 ) and Simpson et al ( 2 ), utilizing large samples from psychiatric emergency departments with suicide outcomes at 30 and 365-days post-discharge, found the Columbia Suicide Severity Rating Scale (C-SSRS) screener to have poor predictive value. Similarly, ( 3 ) found that prior suicidal thoughts and behaviors only provided “marginal improvement in diagnostic accuracy above chance (p. 2).” In the largest meta-analysis to date, covering a span of 50 years, ( 4 ) similarly found: (a) that predictive value has not improved, (b) predictive values are only slightly better than chance across all outcome measures, (c) and ultimately called for fundamental changes in approach to suicide risk assessment, particularly across real-world clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…By their nature, risk factor models can only provide information on mid-term or long-term risk, but not on the risk in a time frame of hours and days. In clinical practice, risk-factor-based suicide screening can be used as an initial step leading to a person-centered risk assessment [ 33 , 34 ].…”
Section: The Limitations Of Theoretical Suicide Modelsmentioning
confidence: 99%
“…Suicide risk assessment is often mandatorily used in psychiatry to predict and prevent suicides. However, suicide risk assessment has such low positive predictive value and limited sensitivity that the clinical value is limited in individual cases and does not justify highly interfering interventions such as admission to inpatient care [30][31][32]. Also, admitting a patient assessed as having high suicide risk to inpatient care has not shown to reduce the incidence of suicides over time and admission to hospital itself has been argued to possibly play a causal role in a proportion of inpatient suicides [32,33].…”
Section: Several Reasons For Non-beneficial Hospital Staysmentioning
confidence: 99%
“…However, suicide risk assessment has such low positive predictive value and limited sensitivity that the clinical value is limited in individual cases and does not justify highly interfering interventions such as admission to inpatient care [30][31][32]. Also, admitting a patient assessed as having high suicide risk to inpatient care has not shown to reduce the incidence of suicides over time and admission to hospital itself has been argued to possibly play a causal role in a proportion of inpatient suicides [32,33]. These unrealistic expectations from society when it comes to psychiatrists' ability to predict and prevent suicides may explain why many psychiatrists experience work-related anxiety related to handling suicidality, sometimes to the extent that it affects their clinical practise negatively [34,35].…”
Section: Several Reasons For Non-beneficial Hospital Staysmentioning
confidence: 99%